2019
DOI: 10.23917/jramathedu.v4i2.8386
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Problem Centered Learning on Student’s Mathematical Critical Thinking

Abstract: Since Indonesian students’ critical thinking skills in junior high school is still in unexpected level, it should be improved through teaching and learning process. The objective of the study is finding out the influence of problem centered learning approach toward students’ mathematical critical thinking ability. Every student should have mathematical critical thinking skills to make mathematics lessons are easier. Using the critical thinking skills will help students improving problem solving skills. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…A conceptual framework of critical thinking can be adopted from the 21st Century Bloom's taxonomy of higher-order thinking skills (Krathwohl, 2002;Himmah et al, 2019). It can serve as a starting point for the development of teaching approaches that foster critical thinking and reasoning (Zapalska et al, 2018;Apriliana, Handayani, & Awalludin, 2019).…”
Section: Disseminating Stagesmentioning
confidence: 99%
“…A conceptual framework of critical thinking can be adopted from the 21st Century Bloom's taxonomy of higher-order thinking skills (Krathwohl, 2002;Himmah et al, 2019). It can serve as a starting point for the development of teaching approaches that foster critical thinking and reasoning (Zapalska et al, 2018;Apriliana, Handayani, & Awalludin, 2019).…”
Section: Disseminating Stagesmentioning
confidence: 99%
“…In addition, Figure 4 reveals that there were 9 pieces of literature where its PBL treatment duration was more than 1 month and less than or equals 3 months. From these literature, four literatures reported that PBL had a moderate effect on students' MCTS (Apriliana et al, 2019;Arviana et al, 2018;Darhim et al, 2020;Sitanggang et al, 2020). Moreover, four other literatures reported that PBL had a strong effect on students' MCTS (Ahdhianto et al, 2020;Alghadari, 2013;Alnita & Arifin, 2017;Ramadhani et al, 2020).…”
Section: Figurementioning
confidence: 98%
“…Some empirical studies related to the PBL implementation for students' MCTS showed that PBL had a strong positive effect on students' MCTS (Ahdhianto et al, 2020;Buana et al, 2020;Ramadhani et al, 2020;Umar et al, 2020;Zetriuslita et al, 2017;Zetriuslita & Ariawan, 2021). Other empirical studies also showed that PBL had a moderate positive effect on students' MCTS (Arviana et al, 2018;Apriliana et al, 2019;Ayuni et al, 2021;Darhim et al, 2020;Haerani et al, 2019;Prihono & Khasanah, 2020;Yolanda, 2019). Some empirical studies, however, revealed that PBL had a modest positive effect on students' MCTS (Hendriana et al, 2013;Islahuddin et al, 2018;Ratnawati et al, 2020;Sunaryo, 2014;Widada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pembelajaran yang dimaksudkan tersebut adalah pembelajaran dengan pendekatan Problem-Centered Learning atau pembelajaran yang berpusat pada masalah. Pendapat ini didukung dengan pernyataan Apriliana et al [7] bahwa Problem-Centered Learning dapat memberikan kesempatan kepada siswa untuk memperoleh, menemukan, mengenali, dan memecahkan masalah yang bersumber dari pengetahuan atau pengalaman siswa, kemudian penyataan Dewanti [8] bahwa pendekatan Problem-Centered Learning merupakan suatu pembelajaran yang senantiasa menghadirkan ide-ide matematika dalam situasi berpusat pada masalah. Serta pernyataan Rinaldi dkk [9] bahwa Problem Centered Learning menjadi pembelajaran yang potensial karena pembelajaran ini ditujukan untuk memperbaiki keadaan pembelajaran yang memungkinkan siswa untuk belajar yang produktif.…”
Section: Pendahuluanunclassified